The triple jump step phase repair flow chart - Schexnayder, B. (Techniques Magazine, 2012)
The second (step) phase of the triple jump has been asource of frustration for generations of jump coaches. Many coaches have sought advice on improving this phase, and I have been personally asked this question hundreds of times. So many coaches are looking for the simple answer or the magic drill. In spite of the fact that this problem has dogged jumps coaches for ages, I have never seen an article or heard a clinic presentation that was based solely on the topic of fixing the step phase. I think the reason this topic has been avoided is, to be simple, it`s complicated. The step phase is a point of collection for all triple jump problems. It effectively serves the same purpose as the "Check Engine" light on your car, signaling a need for a deep, dark and mysterious search through unpleasant countryside for problems. There are probably at least 20 triple jump faults that result in destroyed step phases. Take an athlete who makes two or three mistakes and you are looking for the proverbial needle in the haystack when repairing technique. Combine these issues with the fact that executing the step phase requires the ability to produce huge forces in a fraction of a second. Asking athletes who are not sufficiently trained to do this is a practice doomed to failure, even if technical coaching is sound. The chart provided is designed to work as a roadmap on this search. It provides the coach with a system of analysis and diagnosis for step phase problems, beginning at the step phase takeoff and working back with cause-and-effect methodology. The chart uses a flowchart approach to this diagnostic procedure, requiring certain evaluations to be made and video checkpoints to be analyzed as the roots of these problems are unearthed. This chart might serve as little more than a poor flashlight on this diagnostic journey, but perhaps it can play a small role in the coaching of this event. Great coaches have many such charts in their heads whether they realize it or not. Therefore, more importantly, perhaps it can serve a much larger role by demonstrating the need for and effectiveness of systematic, logic-based coaching and diagnosis in all track & field events.